Effect of WIC Food Package Changes on Dietary Intake of Preschool Children in New Mexico - Morshed, Alexandra B. (Health Behav Policy Rev, 2015)
OBJECTIVES: This study examined WIC policy change effects on dietary intake of preschool children from WIC-participating households in rural New Mexico communities. METHODS: Dietary intake of children enrolled in Head Start in 8 communities was compared before and after 2009 WIC food package changes. RESULTS: Following the policy change, participants reported significantly increased consumption of lower-fat milk, reduced consumption of saturated fat (grams), and decreased consumption of vegetables without potatoes. No significant differences in fruit, fruit juice, vegetables including potatoes, whole-grains and saturated fat (percent-energy) consumption were observed. CONCLUSIONS: WIC policy changes have the potential to improve children’s saturated fat intake. More research with robust designs is necessary to examine long-term effects of WIC policy changes.